More answers

6 + x = -11

6 + x - 6 = - 11 - 6

x = -17

In more detail

First make a mathematical equation from your sentence

6 + x=-11

Now that you have your equation you can solve for 'x'

6+x=-11

-6 -6 (minus 6 from both sides of the equation)

left with x= -17 ( remember a negative plus a negative you get a negative answer)

You can check this by plugging in -17 back in for 'x' in the orginal equation

6+(-17)=-11

6-17=-11

-11=-11

True

therefore x= -17

Hope this helps

Q: What is the answer to 6 plus x equals -11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x + 6

X=5, x+6, 5+6=11

2x - 6 = x + 5 Isolate x. 2x - x = 6 + 5 x = 11

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

x = -6

Related questions

x + 6

x=6

11. cuz 5+6=11

x=-6

X=5, x+6, 5+6=11

2x - 6 = x + 5 Isolate x. 2x - x = 6 + 5 x = 11

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

X = 6

x = -6

The patterns is formed from the product of the first number and the absolute difference of the two numbers. 1 x l4 - 1l = 1 x 3 = 3 3 x l7 - 3l = 3 x 4 = 12 6 x l5 - 6l = 6 x 1 = 6 7 x l10 - 7l = 7 x 3 = 21 11 x l7 - 11l = 11 x 4 = 44

2x+5=11 2x=6 x=3

5x+6-2x=-5-x 3x+6=-5-x 4x=-11 x=11/-4